Impact of Citizenship and Immigration Law on National Security of Nepal - Dahal, Sachin (Unity Journal, 2021)
The citizenship and immigration laws are regarded as the foundational units to assure the security of citizens and also to serve the national integrity. This article discusses about the impact of Nepali citizenship and immigration law on national security of Nepal. What may be the significance of citizenship and immigration law of a nation in an increasingly global society? Has Nepal considered immigration as a threat to security by focusing on societal, economic, internal and public security? In order to elaborate the issues of human security in Nepal from the perspectives of citizenship realm and trends of immigration, it is necessary to investigate the provisions of citizenship provided in the constitution as well as the laws that oversee the effect of immigration on the socio-cultural, political and economic demographics of Nepal. Importance of strong citizenship laws proliferate continuously from dual and transitional citizenship in the context of globalization. Considering the geopolitical location of Nepal and its vulnerability to the possible threats, Nepal’s citizenship and immigration laws have always been the integral part of debate and discussion among the politicians, intellectuals and general public. The development of national security of any country is dependent upon the quality of dignity, liberty and protection ensured to its citizens by the state. So, the economic, social and political rights should be granted to the citizens in equal manner through citizenship while guarding against pretentious foreign interests. Nepal needs to have strong citizenship and immigration laws to sustain its territorial integrity and protect national interests.